Estudo da influência do ferramental na acuracidade de forma de peças de aço ABNT M2,obtidas por usinagem eletroquímica - Pelizer, Mário Cesar (1997)
Shape accuracy was investigated in respect to electrochemical tooling influence on machining of a round groove in speed Steel ABNT M2 bars. Three designs were developed based on conceptions regarding tool movement direction. On first conception tool moves perpendicularly to groove longitudinal axis, and in the second tool moves paralelly to the groove axis. The electrochemical equipment was developded in the Laboratório de Usinagem Não Tradicional do Departamento de Engenharia Mecânica da Universidade Federal de Uberlândia. The equipment is equipped with a tyrestorized pulsed power source of 50 kWA. Shape accuracy was visually evaluated by comparation to a master grooved bar, which was machined by electrical discharge process. The best piece parts were messured to shape runout on a profile machine against a cylinder standard gauge. The most important conclusions obtained from this study are: electrochemical machining must be performed in closed chamber to allow eletrolite pressure control, sodium nitrate is more adequate to machine ABNT M2 steel than sodium cloride and machining equipment must be equipped with a monitorized gap control system to achive good shape accuracy leveis.